Economic Cooperation between Spain and Algeria in the Energy Sector: An Integrated Model for Natural Gas and Renewable Energy: التعاون الاقتصادي بين إسبانيا والجزائر في قطاع الطاقة: نموذج متكامل للغاز الطبيعي والطاقة المتجددة - Lyes Mechakra,; Francisco Jesús Ferreiro Seoane, (Journal of North African Economies, 2025)
Abstract This study aims to analyze the dynamics of energy cooperation between Algeria and Spain through a hybrid model that combines natural gas and renewable energy, within the context of global geopolitical and environmental transitions. A mixed-methods approach was adopted, incorporating quantitative data (from 2013 to 2023) and qualitative analysis (30 interviews with experts and official sources), to provide a comprehensive and accurate understanding of this bilateral cooperation. The findings reveal that Algerian gas remains the backbone of the energy relationship, accounting for 38% of Spain’s energy needs and 22% of Algeria’s national income in 2023. Moreover, the study highlights a 1,300% increase in Algeria’s renewable energy investments over the past decade, reflecting a strategic shift toward clean energy. Economic modeling estimates that the proposed hybrid model could lead to a 25% increase in economic returns by 2030, along with the creation of thousands of direct jobs. The study proposes the establishment of a joint €1 billion investment fund, modernization of existing infrastructure to include green hydrogen transport, and the development of a hybrid electric grid between the two countries. It also calls for enhanced joint scientific research and regulatory harmonization to support energy integration and regional stability. This research contributes a practical and implementable framework for sustainable energy cooperation, offering strategic recommendations grounded in real data and multidimensional analysis. It serves as both an academic and policy reference for researchers and decision-makers across the Mediterranean region.